PROSEDUR PENGUJIAN SUBSTANTIF AKUN PENDAPATAN PT. XYZ OLEH KAP JEPTHA, NASIB DAN JUNIHOL - Lenggo Genni (2021)
The aim of writing this final assignment was to provide information on the substantiating test procedure of the incomes by Public Accounting Firm Jeptha, Nasib and Junihol of the PT. XYZ. The public accountant substantiated a substantive test procedure for studying misrepresentation of material on the credit on an account, as well as testing the reliability of various management statements that had been published to the public. Accounts that have a major impact on the company are income accounts, this is because income accounts have large nominal amounts as a result of interconnectivity between accounts that help each other increase the operational pace of the company's business. Another side of the revenue cycle coming down is the potential misfit on the account, therefore it is important for the company to be the subject of auditing so that the company can improve the business operational efficiency and improve credibility for the financial report. The data extracting methods that the author gets through the interview stages and documentation on every job done, in addition to which the author requires various documents supporting the process such as worksheet, sales invoice, sales order and cash receipt. The end result of the application of substantive testing procedures was one that established that the company has presented financial reports according to common standards of accounting.